INFLUENCE OF IMIDAZOLINES MIXTURES ON THE ACTIVITY OF NADPH-CYTOCHROME C REDUCTASE AND CYTOCHROME P-450 IN A MICROSOMAL FRACTION OF RAT LIVER - Максимова, І.Г. (World of Medicine and Biology, 2016)
The activity of enzymes in a microsomal fraction of rat liver on the 30th day of the effects of industrial chemical pollutants - imidazoline mixtures at doses of 1/10 and 1/100 DL50 was determined with the help of spectrophotometric method, which was necessary for the complete explanation of the biochemical mechanisms of their membrane-tropic action. Imidazoline-containing mixtures with alkyl radicals C7-9 and C9-15 at a dose of 1/10 DL50 cause inactivation of microsomal NADPH reductase system, proven by reduced activity of NADPH-cytochrome c reductase and decrease in cytochrome P-450 level. On the contrary, prolonged exposure of mixtures at a dose of 1/100 DL50 leads to its activation, as evidenced by increased activity of NADPH-cytochrome c reductase and level of cytochrome P-450. The revealed changes can be considered as one of the pathogenetic links of biochemical mechanisms of the membrane-tropic action of imidazoline mixtures that need to be taken into account in the development of methods for their correction.